2016
DOI: 10.1111/acer.13008
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Toxicity in Diabetes and Its Complications: A Double Trouble?

Abstract: This review summarizes the epidemiology, diagnosis, pathophysiology, metabolic, and cell signaling alterations and finally brushes upon issues and strategies to manage the "double trouble."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 99 publications
1
28
0
1
Order By: Relevance
“…However, this interaction was not significantly related to incident retinopathy and nephropathy. Past research has shown that heavy alcohol use and high depressive symptoms are each independently positively related to neuropathy and heart disease . The present study adds to the literature by demonstrating that the combination of high depressive symptoms and high alcohol frequency may lead to an even greater risk of neuropathy and CAD.…”
Section: Discussionsupporting
confidence: 60%
See 3 more Smart Citations
“…However, this interaction was not significantly related to incident retinopathy and nephropathy. Past research has shown that heavy alcohol use and high depressive symptoms are each independently positively related to neuropathy and heart disease . The present study adds to the literature by demonstrating that the combination of high depressive symptoms and high alcohol frequency may lead to an even greater risk of neuropathy and CAD.…”
Section: Discussionsupporting
confidence: 60%
“…Several possible mechanisms may link alcohol consumption to diabetes‐related complications . Whereas acute alcohol consumption may not have any significant long‐term effects on glucose in individuals with T2DM, chronic heavy alcohol use may result in changes in glucose levels, insulin resistance, changes in lipid levels, mitochondrial dysfunction, and interference in cell signalling .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[3]. Among these factors, the associations between alcohol drinking and T2DM have been widely studied [4,5]. More alcohol consumption may relate to higher susceptibility to T2DM.…”
Section: Introductionmentioning
confidence: 99%